Social issues in general practice – a survey assessing the interprofessional perspective of general practitioners and social workers regarding frequency, challenges, and needs - Tonia Gerber; Laura Diaz Hernandez; René Rüegg; Dunja Vetter; Andreas Zeller (BMC Primary Care)
Abstract Background Health or illness and social issues cannot be viewed in isolation. Social problems can influence well-being and disease. General Practitioners (GPs) are requested to offer counselling opportunities to respond to the social issues of their patients adequately. Counselling on non-medical issues in general practice increases GPs’ workload. The study aimed to analyse the occurrence of social problems as well as the strengths and weaknesses of existing working agreements between social services and GPs in primary care. Methods We carried out a cross-sectional online survey between December 2022 and January 2023 among a sample of Swiss GPs from the Sentinella-Network, the uniham-bb-Network and social workers from the SAGES-Network. Results Findings come from a sample of 143 GPs (mean age 54 years, 37.8% female) and 41 social workers (mean age 43 years, 75.6% female). GPs face a median of 3 patients with social problems per week (IQR 5.2). They reported encountering patients facing “Finance” issues most frequently, with 78.8% encountering such cases between “more than 3 patients per week” and “1–3 patients per month”. “Work” (76.4%) and “Loneliness” (73.7%) were also among the most commonly encountered social problems. When suspecting the problem, GPs more often addressed the issue if it was about “Addiction” (83.2%), “Loneliness” (72.3%), or “Protection” (71.4%). More than half of GPs (56.0%) reported having contact with social workers less than once a month, while approximately half of the social workers reported having contact with GPs 1 to 3 times a month (48.7%). GPs (69.3%) and social workers (76.3%) would like more contact. The most frequently mentioned benefits of an increased collaboration from the GPs’ perspective were “improved quality of care (more time for medical issues)” (64.8%) and “improved mental health of patients” (55.6%). Conclusions Social problems in general practice are common, but the interprofessional cooperation between GPs and social workers is scarce. However, both parties appear to be in favour of closer interprofessional collaboration and seem to be willing to attempt to improve joint patient care in the future. The integration of social workers into general practice is promising for a comprehensive, interprofessional, and preventative patient approach to providing the best healthcare.